Human Development To Democracy: An Impact Analysis of Poverty and Income Inequality In Indonesia - Fadly, Fajar; Chandra, Ade (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Research Originality: The research looks at the relationship and impact of welfare indicators on the implementation of democracy in Indonesia. Previous research concentrated on the impact of democracy implementation.Research Objectives: This study aims to examine the role of public welfare variables in improving the implementation of democracy in Indonesia.Research Methods: The study used panel data with a multiple regression approach from 34 provinces from 2009 to 2023 with the Fix Effect Model (FEM) category.Empirical Results: The research findings show that the public welfare variable has a significant effect on the democracy index in Indonesia both partially and simultaneously, and only the human development index and the democracy index are linearly related. It was found that the human development index variable is an intermediary variable influencing the relationship between income inequality and the democracy index.Implications: To increase people's understanding of democracy, the government can lower the poverty depth index because there is no intermediate variable between the two variables.JEL Classification: C33, D72, Z13, Z18